Atherosclerosis amelioration by allicin in raw garlic through gut microbiota and trimethylamine-N-oxide modulation - Panyod, Suraphan; Wu, Wei-Kai; Chen, Pei-Chen; Chong, Kent-Vui; Yang, Yu-Tang; Chuang, Hsiao-Li; Chen, Chieh-Chang; Chen, Rou-An; Liu, Po-Yu; Chung, Ching-Hu; Huang, Huai-Syuan; Lin, Angela Yu-Chen; et al. (NPJ biofilms and microbiomes, 2022)
Cardiovascular disease (CVD) is strongly associated with the gut microbiota and its metabolites, including trimethylamine- N -oxide (TMAO), formed from metaorganismal metabolism of ʟ-carnitine. Raw garlic juice, with allicin as its primary compound, exhibits considerable effects on the gut microbiota. This study validated the benefits of raw garlic juice against CVD risk via modulation of the gut microbiota and its metabolites. Allicin supplementation significantly decreased serum TMAO in ʟ-carnitine-fed C57BL/6 J mice, reduced aortic lesions, and altered the fecal microbiota in carnitine-induced, atherosclerosis-prone, apolipoprotein E-deficient (ApoE −/− ) mice. In human subjects exhibiting high-TMAO production, raw garlic juice intake for a week reduced TMAO formation, improved gut microbial diversity, and increased the relative abundances of beneficial bacteria. In in vitro and ex vivo studies, raw garlic juice and allicin inhibited γ-butyrobetaine (γBB) and trimethylamine production by the gut microbiota. Thus, raw garlic juice and allicin can potentially prevent cardiovascular disease by decreasing TMAO production via gut microbiota modulation.